Employee’s Perception of Performance Management System – An Assessment - Panda, Sitansu; Nazarudin, Bujang (Universiti Tenaga Nasional, 2016)
Performance Management System (PMS) is an important component of Human Resource Management (HRM). The purpose of PMS is to evaluate and integrate the doables and deliverables in organization. The successful implementation of PMS helps in the attainment of organizational goals. The contribution of the organizational members and their perception about PMS has a key role to play for achieving the goals of PMS. In this context, the paper addresses to the employees’ perception about PMS of the organization. The significant variation between the perceived values of the employees about PMS and its different dimensions is explored in this study. The supervisor’s motivational and empathetic role, upward communication in organization, conducting Training & Development (T & D) programmes for achieving PMS goals have been suggested.